An Energy and Ecological Assessment of The Prior and Post-Hybrid Renovation State of Multi-Dwelling Building in the Algerian City of Skikda - Khelfa, Imed eddine; Lazri, Youcef; Alkama, Djamel; Toumi, Riad (Indonesian Journal of Social Science Research, 2024)
In the context of Algerian energy and environmental concerns and its aspirations for energy transition, this article examines the pre- and post-state of a multi-family residential building in the city of Skikda, in northern Algeria, utilizing the UBEM reduced-order approach, alongside QGIS, CEA and METEONORM tools. Primarily focusing on the building's solar exposure, energy aspects, and environmental considerations. Six hybrid renovation scenarios were considered then, and assessed for their contribution for energy savings and ecological improvement. The main results revealed that 87% of annual energy requirements were related to heating and hot water, which are supplied by a natural gas system, a source of various types of greenhouse gases, which suggested the use of triple glazing, with or without two selective low-emissivity coatings only, or be combined by changing hot-water supply system to an electric one, alongside the installation of the hybrid PVT panels on the south façade. This triple glazing was joint in another scenario by integrating the same type of panels on the roof alongside a seasonal thermal energy storage system. This latter scenario being the best in terms of energy and ecology, and making the building highly performant in both aspects.